MULTICULTURALISM AND TRANSDISCIPLINARITY: AN EPISTEMOLOGICAL PROPOSAL FOR IAIN MANADO’S MULTICULTURALISM - Sulaiman Mappiasse (Potret Pemikiran, 2019)
Since 2017, IAIN Manado has embraced multiculturalism as a core value for its vision to become an excellent Islamic higher education institution in Southeast Asia in 2035. This policy has however been taken without prior wide scholarly discussions. Consequently, the internalization and translation of this value into IAIN’s processes of education are facing some difficulties. This paper proposes a conceptual framework around multiculturalism and transdisciplinarity for IAIN Manado in its attempt to develop competitiveness. It argues that the notion of multiculturalism is always political so that IAIN Manado may develop its own concepts and practices of multiculturalism. It also argues that in order for IAIN Manado to accomplish the implementation of its multiculturalism as a culturally epistemological vision, it should consider the espousal of transdisciplinarity as an academically epistemological vision. Keywords: Multiculturalism; Transdisciplinarity; Vision; IAIN Manado Sejak 2017, IAIN Manado telah memilih multikulturalisme sebagai nilai utama dari visinya untuk menjadi perguruan tinggi Islam unggul di Asia Tenggara pada tahun 2035. Namun demikian, kebijakan ini telah diambil tanpa didahului diskusi-diskusi luas yang melibatkan para ahli. Akibatnya, internalisasi dan realisasi nilai ini ke dalam proses pendidikan di IAIN Manado mengalami berbagai kesulitan. Artikel ini mengajajukan kerangka konseptual tentang multikulturalisme dan transdisiplinaritas untuk IAIN Manado dalam usahanya mengembangkan daya saing. Artikel ini berargumen bahwa konsep multikulturalisme selalu bersifat politis sehingga IAIN Manado dapat mengembangkan konsep dan praktik multikulturalnya sendiri. Selain itu, untuk menyempurnakan implementasi visi multikuluralnya sebagai sebuah visi epistemologis secara budaya, IAIN Manado sebaiknya mempertimbangkan untuk mengadopsi transdisiplinaritas sebagai sebuah visi epistemologis secara akademik. Kata Kunci: Multikulturalisme; Transdisiplinaritas; Visi; IAIN Manado